The Development of the Business Rules Diagram - McDermid, Donald (Curtin University, 1998)
This thesis concerns the development of a diagramming technique which assists in the specification of information systems requirements. The technique is called the Business Rules Diagram (BRD) although earlier versions were given different names. The term development in the title of this thesis is defined here to include both the work involved in designing the BRD as well as testing its usefulness. So, the scope of this research covers research activity starting from the original idea for the diagram through to testing its usefulness.Action research was the research method used. In all, two major action research studies were undertaken. The first involved working with an analyst only. The second involved working with an analyst and users.